Low bone mineral density and calcium intake in elite cyclists - Medelli, J.; Shabani, M.; Lounana, J.; Fardellone, P.; Campion, F. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. High physical activity is associated with larger bone mineral content (BMC) and density (BMD) in young males though competitive road cyclists have been reported to have similar or lower BMD than controls. Methods. BMC and BMD were assessed in 73 highly trained (42 professional and 31 elite amateur) road cyclists (CYCLIST; age: 25.8±4.3 years; height: 179.7±6.3 cm; weight: 71.6±6.3 kg; %Fat mass: 9.5±3 %; VO2max: 68.5±5.7 ml/kg·min) and in 30 healthy males used as reference (REF: 28.3±4.5 years; 176.6±6.2 cm; 74.5±8.4 kg; 21.3±6.1%). Results. Daily calcium intake estimated from a food-questionnaire was higher in CYCLIST than in REF (942±374 vs 753±315 mg/d; P=0.008). Compared to REF, CYCLIST had lower L1-L4 BMD (1.004±0.125 vs 1.240±0.163 g·cm-2; P<0.0001) and femoral neck BMD (0.986±0.132 vs 1.098±0.137; P<0.003). In CYCLIST, daily calcium intake is correlated with total BMC and BMD (r=0.27-0.26, P=0.02) and femoral BMD (r=0.35; P=0.002). Divided by tertiles (high, medium and low Ca), CYCLIST with high Ca (1320±382 mg·d-1) had lower lumbar BMD values (-6.68%; P=0.02) and tended to have lower femoral neck BMD (-4.77%; P=0.09) and radius UD BMD (-5.9%; P=0.07) than REF. Conclusion. There was no difference between medium Ca and high Ca for any BMC or BMD parameters. Differences between low Ca and high Ca could be detected only for Total BMC (-8.4%; P=0.01), Pelvis BMD (-7.4%; P=0.01) and femoral neck BMD (-9.9%; P=0.006).